2016
DOI: 10.1016/j.ijporl.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ear canal static pressure on the dynamic behaviour of outer and middle ear in newborns

Abstract: Please cite this article as: V. Aithal, J. Kei, C. Driscoll, M. Murakoshi, H. Wada, Effects of ear canal static pressure on the dynamic behaviour of outer and middle ear in newborns, International Journal of Pediatric Otorhinolaryngology (2015), http://dx.doi.org/10. 1016/j.ijporl.2015.12.006 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typeset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The resonance frequencies calculated from Model 3 in each oscillating mode ranged from 274.21 Hz to 319.22 Hz with an average frequency of about 290 Hz (Table 3). These frequencies fell within the range of the low-frequency resonance found in neonates, i.e., about 200-450 Hz (Aithal et al, 2016a(Aithal et al, , 2016b(Aithal et al, , 2015(Aithal et al, , 2014Holte et al, 1991;Keefe et al, 1993;Meyer et al, 1997;Murakoshi et al 2013).…”
Section: Dynamic Characteristics Of the Neonatal External Ear Canal (mentioning
confidence: 55%
See 1 more Smart Citation
“…The resonance frequencies calculated from Model 3 in each oscillating mode ranged from 274.21 Hz to 319.22 Hz with an average frequency of about 290 Hz (Table 3). These frequencies fell within the range of the low-frequency resonance found in neonates, i.e., about 200-450 Hz (Aithal et al, 2016a(Aithal et al, , 2016b(Aithal et al, , 2015(Aithal et al, , 2014Holte et al, 1991;Keefe et al, 1993;Meyer et al, 1997;Murakoshi et al 2013).…”
Section: Dynamic Characteristics Of the Neonatal External Ear Canal (mentioning
confidence: 55%
“…To extend its versatility, the SFI meter has been redesigned, and SFI tests were performed in neonates. As a result, the SPL was found to show two variations, one at around 0.3 kHz and the other at around 1.2 kHz (Aithal et al, 2016a(Aithal et al, , 2016b(Aithal et al, , 2015(Aithal et al, , 2014Murakoshi et al, 2013). Since the SPL shows a variation at 1.3 0.3 kHz due to the resonance of the middle ear in normal-hearing adults and children (Zhao et al, 2002), the variation found at around 1.3 kHz is probably related to such resonance in neonates.…”
Section: Introductionmentioning
confidence: 92%
“…As illustrated in Figure 1B, Murakoshi et al (2012) and Aithal et al (2016) noted that the second resonance (RF2) disappeared in newborns with middle ear dysfunction while the first resonance (RF1) was not affected. These results indicated that middle ear dysfunction altered the dynamic behavior of the middle ear to such an extent that the second resonance could not be detected using the SFI meter.…”
mentioning
confidence: 88%
“…The greatest variations of SPL (DSPL) occur at median frequencies of RF1 and RF2 along the SPL curve (at ambient pressure of 0 daPa) which are considered the RF of the ear canal and middle ear, respectively (Wada et al, 1995;Murakoshi et al, 2013). In comparison, the SFI results for a newborn, who failed in HFT and TEOAE, reveal only one variation at RF1 (Aithal et al, 2016) ( Figure 1B).…”
mentioning
confidence: 97%
See 1 more Smart Citation